Polyvinylsulfonic acid: A Low-cost RNase inhibitor for enhanced RNA preservation and cell-free protein translation. Issue 1 (1st January 2018) - Earl, Conner C.; Smith, Mark T.; Lease, Richard A.; Bundy, Bradley C.
ABSTRACT: The effectiveness and economics of polyvinyl sulfonic acid (PVSA) as a ribonuclease inhibitor for in vitro systems is reported. PVSA was shown to inhibit RNA cleavage in the presence of RNase A as well as in the presence of Escherichia coli lysate, suggesting that PVSA can act as a broader ribonuclease inhibitor. In addition, PVSA was shown to improve the integrity of mRNA transcripts by up to 5-fold in vitro as measured by their translational viability. Improved preservation of mRNA transcripts in the presence of PVSA under common RNA storage conditions is also reported. A cost comparison with commercially available RNAse inhibitors indicates the economic practicality of PVSA which is approximately 1, 700 times less expensive than commonly used ribonuclease inhibitors. PVSA can also be separated from RNA by alcohol precipitation for applications that may be sensitive to the presence of PVSA.